Determination of the crack resistance curve for intralaminar fiber tensile failure mode in polymer composites under high rate loading. (15th November 2018) - Kuhn, P.; Catalanotti, G.; Xavier, J.; Ploeckl, M.; Koerber, H.
Abstract: This paper presents the determination of the crack resistance curve of the unidirectional carbon-epoxy composite material IM7-8552 for intralaminar fiber tensile failure under dynamic loading. The methodology, proposed by Catalanotti et al. (2014) for quasi-static loading conditions, was enhanced to high rate loading in the order of about 60  s −1 . Dynamic tests were performed using a split-Hopkinson tension bar, while quasi-static reference tests were conducted on a standard electromechanical testing machine. Double-edge notched tension specimens of different sizes were tested to obtain the size effect law, which in combination with the concepts of the energy release rate is used to measure the entire crack resistance curve for the fiber tensile failure mode. Digital image correlation is applied to further verify the validity of the experiments performed at both static and dynamic loading. The data reduction methodology applied in this paper is suitable for intralaminar fiber failure modes without significant delamination. Sufficient proof is given that quasi-static fracture mechanics theory can also be used for the data reduction of the dynamic tests. It is shown, that the intralaminar fracture toughness for fiber tensile failure of UD IM7-8552 increases with increasing rate of loading.